A n investigation into the use of shadowing technique in listening lessons to improve the pronunciation of 3rd year students at HUBT (Hanoi University of Business and Technology) = Nghiên cứu việc sử dụng thủ thuật nghe và nhắc lại đồng thời trong giờ học - Mai, Thị Vân Anh (University of Languages and International Studies, 2017)
43 p. + CD-ROM + Tóm tắt